Análise de valor percebido em produtos sustentáveis provenientes da logística reversa - Gubert, Flávia (My University, 2017)
Increasing use of raw materials and concern for the environment has encouraged organizations to restructure their logistics processes, which means planning and introducing the Reverse Logistics system as a complement to this process. The use of the material to be recycled, reused or remanufactured, as well as forwarding it to its proper disposal, has made Reverse Logistics collaborate to reduce the environmental impact. This implies minimizing costs during the production process, saving material and natural resources. Therefore, the objective of this dissertation is to measure the perception of value in products from Reverse Logistics from the perspective of the producer and internal customer. For that, a quantitative exploratory descriptive research was developed with the managers and internal customers of a company that manufactures and markets products from plastic, located in the Campos de Cima of the Serra do Rio Grande do Sul. Through a survey, whose data were collected with the completion of a questionnaire answered by the internal clients and managers, in order to verify the perceived value of the products coming from the practice of Reverse Logistics. The results indicate that the perceived value in reverse logistics is determined by three factors: quality, production techniques and product prices.
A crescente utilização de matéria prima e a preocupação com o meio ambiente instigaram as organizações a reestruturar seus processos logísticos, o que implica em planejar e introduzir o sistema de Logística Reversa como complemento deste processo. O aproveitamento do material para ser reciclado, reutilizado ou remanufaturado, bem como encaminhá-lo ao seu descarte adequado, fez com que a Logística Reversa colaborasse para a redução do impacto ambiental. Isso implica em minimizar custos durante o processo produtivo, economizando recursos materiais e naturais. Diante disso, o objetivo desta dissertação é medir a percepção de valor em produtos provenientes de Logística Reversa sobre a perspectiva do produtor e cliente interno. Para tanto, desenvolveu-se uma pesquisa quantitativa de caráter exploratório descritiva com os gestores e clientes internos de uma empresa que fabrica e comercializa produtos provenientes do plástico, situada nos Campos de Cima da Serra do Rio Grande do Sul. A pesquisa realizada foi operacionalizada por meio de uma survey, cujos dados foram coletados com o preenchimento de um questionário respondido pelos clientes internos e gestores, a fim de verificar o valor percebido dos produtos advindos da prática da Logística Reversa. Os resultados indicam que o valor percebido na logística reversa é determinado por três fatores: qualidade, técnicas de produção e preço dos produtos.
Keywords: Logística; Cadeia de suprimentos; Meio ambiente; Sustentabilidade; Logistics; Supply Chain; Environment; Sustainability